1998
DOI: 10.1097/00003446-199802000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Click Polarity May Uncover Auditory Neuropathy In Infants

Abstract: Comparing responses with positive versus negative polarity clicks may help separate ABRs from cochlear potentials and alert clinicians to the possibility of an auditory neuropathy. Therefore, absent or abnormal ABRs in the presence of normal otoacoustic emissions need not always implicate a purely "central disorder," but might be consistent with dysfunction between outer hair cells and primary afferent fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
3
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 30 publications
5
115
3
2
Order By: Relevance
“…The recording amplitude is increased, compared to ABEP testing, by locating the electrodes closer to the site of origin of cochlear potentials, which is extremely relevant in AN/AD, as published papers have shown that CMs are ampler in such testing conditions. [22][23][24][25][26] Higher quality recordings make it possible to evaluate not only the amplitude but also the duration of CMs; the literature suggests that CMs are more prolonged in AN/AD, compared to normal subjects.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recording amplitude is increased, compared to ABEP testing, by locating the electrodes closer to the site of origin of cochlear potentials, which is extremely relevant in AN/AD, as published papers have shown that CMs are ampler in such testing conditions. [22][23][24][25][26] Higher quality recordings make it possible to evaluate not only the amplitude but also the duration of CMs; the literature suggests that CMs are more prolonged in AN/AD, compared to normal subjects.…”
Section: Resultsmentioning
confidence: 99%
“…When OAEs are absent in these patients, however, the differential diagnosis depends on CM recordings. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]20,21 It seems inappropriate to analyze CMs by using ABEP testing for the following reasons: the stimulus (click) that is used to initiate neural potentials limits the conditions for recording CMs; 1,20,25,34 and secondly, many clinicians perform ABEP testing with supra-aural phones,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations